Awareness and preparedness in smoking cessation among smoker patients scheduled for elective surgery in HUSM - Sulaiman, Al Jadidi (2016)
Background: Smoking is the single most cause of preventable disease and premature death. Perioperative smoking is linked to various complications and morbidity and to a significant economic burden. Elective surgery offers a powerful opportunity for surgeon and anesthetist to help smokers quit. This study set out to identify factor or predictor toward smoking cessation among smoker patients prior to scheduled surgery; and to determine how sociodemographic background, smoking status and knowledge on the health risks of smoking contribute toward development of such attitude. Methodology: 106 smoker patients who scheduled for elective surgery in Hospital Universiti Sains Malaysia were enrolled from April till September 2015. This paper reports the results of a cross-sectional study on these patients by filling predetermined questionnaire before anesthesia and surgery or on the first operative day. The survey included three sections exploring demographical profile of respondent, smoking status and knowledge regarding smoking-related risks. Results: Mean age of respondent was 37 (SD, 17.3). 60.4% (n=64) patients stopped smoking more than 24 hour prior to surgery while the other 39.6% (n=42) had cessation less than 24 hour preoperatively. Intention to quit turned out to be the mostsignificant predictor for early smoking cessation in this study. Smoker patients who did not have intention to stop smoking had 4.32 higher odds of cessation less than 24 hour compare to those who had intention to stop smoking (95% CI: 1.85, 10.10, pvalue< 0.001). Conclusion: Considering many beneficial effects of preoperative smoking cessation, both surgeon and anesthetist should play their role to achieve this; to the least of brief smoking cessation advice, and to the extent of any form of smoking cessation interventions. Introduction of nicotine replacement therapy will double the chance of abstinence and cure among smokers. Keywords: Smoking cessation, Elective Surgery, Awareness, Preparedness